DINAMIKA KELOMPOK TANI KARET DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Andre Marta Yoppi; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to: 1) Knowing the internal factors and external faktors of rubber farmer groups; 2) Knowing the dynamics of rubber farmer groups. This research is done with survey method and sampling as many as 60 ​​samples. Analysis of the data using The Likert Scale's Summated Ratting (SLR).The results showed that internal factors of groups rubber farmer in a medium category and external factors of group rubber farmer in a high category. The groups dynamics farmer in a high category.   Keywords : Groups dynamics, Farmer groups, Rubber Farmer